The Effect of FOMO (Fear of Missing Out) on Social Media on Insomnia: A Literature Review - Al Habsyi, Alya Raguan; Fahma, Hilmia (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
Background: FOMO is an anxiety that a person feels when they feel left out of the experiences shared by others on social media. In today's digital era, social media has become an important element in everyday life. The phenomenon of Fear of Missing Out (FOMO) is emerging as a significant negative impact, potentially disrupting individuals' mental health and sleep quality including insomnia. Objectives: This study aimed to explore the relationship between FOMO and insomnia and provide recommendations for management of social media use to improve sleep quality. Methods: A literature review was conducted through analyzing literature from Google Scholar, Pubmed, and Mendeley (2019-2024) with a focus on the keywords FOMO, insomnia, and mental health. Results: Findings suggest that FOMO contributes to sleep difficulties and decreased sleep quality. High social media use, especially at night, correlated with increased anxiety and sleep difficulties. The study also identified mechanisms such as rumination and negative emotional affect as factors that exacerbate insomnia among individuals experiencing FOMO. Conclusion: There is an association significant between FOMO (Fear of Missing Out) and insomnia, where anxiety due to FOMO disrupts sleep patterns. Therefore, implementing management strategies such as limiting social media use before bedtime is essential to improve sleep quality and reduce the negative impact of FOMO. Keywords: Insomnia, FOMO, Social Media